The Indian enigma revisited - Liza von Grafenstein; Stephan Klasen; John Hoddinott (Georg-August University of Göttingen, RTG 2654 Sustainable Food Systems, 2022)
This paper re-enters the contested discussion surrounding the Indian Enigma, the high prevalence of chronic undernutrition in India relative to sub-Saharan Africa. Jayachandran & Pande argue that the key to the Indian enigma lies in the worse treatment of higher birth order children, particularly girls. Analyzing new data, we find: (1) Parameter estimates are sensitive to sampling design and model specification; (2) The gap between the heights of pre-school African and Indian children is closing; (3) The gap does not appear to be driven by differential associations by birth order and child sex; (4) The remaining gap is associated with differences in maternal heights. If Indian women had the heights of their African counterparts, pre-school Indian children would be taller than pre-school African children; and (5) Once we account for survey design, sibling size and maternal height, the coefficient associated with being an Indian girl is no longer statistically significant.
Keywords: I12; I15; J13; O12; O15; O57; Z13; 330; Nutrition; India; sub-Saharan Africa; Height; India Enigma